Evaluation of the Use of Periodicals Collection of the Higher Education Council Documentation and Online Search Center: Arts and Humanities Periodicals - Elçin Özbudak (Türk Kütüphaneciliği)
Evaluation of the use perodicals collections in libraries is important as perodicals report the results of the latest scientific research and they are usually more expensive than other types of library materials. In this study we evaluate the use of Arts and Humanities periodicals in the collection of the Higher Education Council Documentation Center. Although the use of Arts and Humanities periodicals was found to be lower than, say, Biomedical periodicals collection, the number of journal titles in Arts and Humanities appears to be quite satisfactory. Some suggestions are made so as to increase the use of Arts and Humanities periodicals collection.